The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3389/fmolb.2021.780329
|View full text |Cite
|
Sign up to set email alerts
|

An Unfolded Protein Response Related Signature Could Robustly Predict Survival Outcomes and Closely Correlate With Response to Immunotherapy and Chemotherapy in Bladder Cancer

Abstract: Background: The unfolded protein response (UPR) plays a significant role in maintaining protein hemostasis in tumor cells, which are crucial for tumor growth, invasion, and resistance to therapy. This study aimed to develop a UPR-related signature and explore its correlation with immunotherapy and chemotherapy in bladder cancer.Methods: The differentially expressed UPR-related genes were put into Lasso regression to screen out prognostic genes, which constituted the UPR signature, and were incorporated into mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 60 publications
1
6
0
Order By: Relevance
“…The mean TMB score of cluster 1 was substantially higher than that of cluster 2. A high TMB score was positively associated with the immunotherapy response rate, which also supported our hypotheses ( 35 ). Inadequate nutrient supply and hypoxia caused by inadequate nutrient supply and hypoxia promote enrichment of cancer stem cells ( 12 , 36 ).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The mean TMB score of cluster 1 was substantially higher than that of cluster 2. A high TMB score was positively associated with the immunotherapy response rate, which also supported our hypotheses ( 35 ). Inadequate nutrient supply and hypoxia caused by inadequate nutrient supply and hypoxia promote enrichment of cancer stem cells ( 12 , 36 ).…”
Section: Discussionsupporting
confidence: 89%
“…Cluster 1 had a statistically higher mRNAsi score than cluster 2, which also supported that patients in the cluster 1 were more likely to benefit from immunotherapy. Given the results of TMB and mRNAsi, patients with high microsatellite instability (MSI) scores could benefit more from immunotherapy ( 35 ). The comparison results of the MSI Expr Sig score between the clusters supported that patients in the cluster 1 were more likely to benefit from immunotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…The analysis of immune cell infiltration suggested that the high‐risk group had a higher infiltration of M0 macrophages and plasma cells, while T follicular helper cells were more abundant in low‐risk group. The high proportion of M0 macrophages, indicating a higher level of inflammatory activation, was correlated with poor prognosis of BC patients 46,47 . It has previously been reported that more recruitment of naïve M0 macrophages is associated with early LNM, which could prevent T cells from attacking tumor cells and secrete growth factors promoting tumor angiogenesis 48,49 .…”
Section: Discussionmentioning
confidence: 96%
“…The high proportion of M0 macrophages, indicating a higher level of inflammatory activation, was correlated with poor prognosis of BC patients. 46 , 47 It has previously been reported that more recruitment of naïve M0 macrophages is associated with early LNM, which could prevent T cells from attacking tumor cells and secrete growth factors promoting tumor angiogenesis. 48 , 49 T follicular helper cells might contribute to the maintenance of a protective immune response, which was proved to be associated with better prognosis in BC.…”
Section: Discussionmentioning
confidence: 99%
“…The mRNA expression profiles and corresponding clinical features of 85 osteosarcoma patients were acquired from the TARGET database as a training cohort ( https://ocg.cancer.gov/ programs/target). UPRRGs were extracted from hallmark gene sets from the Molecular Signature Database ( Zhang et al, 2021 ). In addition, mRNA expression profiles and relevant clinical information of 53 osteosarcoma patients from GSE21257 were obtained from the GEO database to serve as an external validation cohort ( https://www.ncbi.nlm.nih.gov/geo/ ).…”
Section: Methodsmentioning
confidence: 99%